Dasar-Dasar Penyuluhan Islam - Enjang AS (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2009)
One of da’wah form that can't forgotten its function for people development called Islamic counselling( irsyad ). The practice of this da’wah form need to be done with professional's manner, because in fact although task of frequent counselling entrusted with prominent of religion, but then if look to development goals attainment therefore that professionalism charge still has continually be built and  developed. At least, there  are three  available unsure that important to be made as counselling basic: (1 ) People have to know what do be passed on extension agents, (2 ) People have to know why such a that something, and (3 ) people have to want and able to do that something.